Organizing the Special Preschool. Module 1 - Harper-Whalen, Susan; Spiegle-Mariska, Jan; Montana Univ., Missoula. Div. of Educational Research and Services ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1991)
The classroom teacher in preschool special education must focus attention in several areas in order to create a smoothly operating and effective classroom environment. Because most of the learning experiences provided for young children are dependent upon interaction with materials, attention must first be given to purchasing and gathering materials. Communication among team members (including families) within the preschool environment must also be considered. The physical layout of the classroom is an important influence on behavior and learning. Proposed learning centers include a block play area, dramatic play area, trough and science area, large motor area, art area, writing area, and library/listening area. Classroom management strategies should be established to ensure a safe learning environment for young children. Appendices contain a checklist of things that need to be done before school starts, a preschool philosophy statement, child information sheet, weekly newsletter sample, sample daily classroom schedule, sample floor plan, and other administrative materials. (JDD)
Sponsoring Agency: Special Education Programs (ED/OSERS), Washington, DC. Handicapped Children's Early Education Program.
Contract Number: H024D00029.
ERIC Note: A product fo the CO-TEACH Preschool Program.
Teachers.
Practitioners.
May also be available online. Address as at 14/8/18
Keywords: Classroom Design; Classroom Environment; Classroom Techniques; Disabilities; Early Intervention; Educational Planning; Instructional Materials; Interpersonal Communication; Learning Centers (Classroom); Parent Teacher Cooperation; Preschool Education; Guides, Non-Classroom.